The factors that influence the awareness of personal health budget among students Faculty of Business Management of UiTM Malacca City Campus / Tengku Norashikin Tengku Yunus - Tengku Yunus, Tengku Norashikin (2014)
This research is focus on factors that influence personal health budget among students. The factors that have been studied are media awareness, personal lifestyle and medical cost. Media can influence people since media is so much a part of our everyday lives and people contact with it so often. The media comes in many different forms such as newspaper, televisions, radios, internets, books, magazines and advertisements. The media is one of the most powerful factors because media plays a big role in how people interpret, understand and learn about ourselves and the world around us. Media also is one of the biggest contributors to culture in our society since it sends us a ton of messages every day. Lifestyle defines as a set of attitudes, habits or possessions associated with a particular group or person, Lifestyle can be healthy or unhealthy based on food choices, activity level and behaviour. Having a positive lifestyle can bring a happiness while negative lifestyle can lead to sadness, illness and depression. Medical cost or medical expenses is an any cost incurred in the prevention or treatment of injury or diseases. These expenses include payments for legal medical services rendered by physicians, surgeons, dentists and other medical practitioners. They include the costs of equipment, supplies, and diagnostic devices needed for these purposes.